2010
DOI: 10.1001/archpediatrics.2010.104
|View full text |Cite
|
Sign up to set email alerts
|

Active Video Games to Promote Physical Activity in Children and Youth

Abstract: To systematically review levels of metabolic expenditure and changes in activity patterns associated with active video game (AVG) play in children and to provide directions for future research efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
354
1
20

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 480 publications
(388 citation statements)
references
References 67 publications
(123 reference statements)
13
354
1
20
Order By: Relevance
“…68,69 Several of these technologies also offer Internet connectivity, including Nintendo Wii Fit and Microsoft Kinect, and the ability to join an online gaming service that allows one to play games against other members in its online community with the use of an avatar. A recent study of the effects of the exergaming experience 70 found that seeing the image of self January 15, 2013 on screen works positively for individuals with low body image but works negatively for individuals with high body image.…”
Section: Other Social Media Technologiesmentioning
confidence: 99%
“…68,69 Several of these technologies also offer Internet connectivity, including Nintendo Wii Fit and Microsoft Kinect, and the ability to join an online gaming service that allows one to play games against other members in its online community with the use of an avatar. A recent study of the effects of the exergaming experience 70 found that seeing the image of self January 15, 2013 on screen works positively for individuals with low body image but works negatively for individuals with high body image.…”
Section: Other Social Media Technologiesmentioning
confidence: 99%
“…Indeed, there is some evidence that electronic games may be beneficial for youth (e.g., modeling of prosocial behaviors, improving cognitive performance and learning) 25 . Furthermore, compared with sedentary video games, several new active video games increase energy expenditure 26 and therefore a distinction should be made between active and inactive video games, since each game may have a different impact on health. Unfortunately, however, the current study did not distinguish between time spent on active and inactive electronic games.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have found that video game use was associated with obesity in children independent of time spent watching television and physical activity [2,3]. Additionally, health-oriented gaming interventions have been primarily tested in children [4,5]. Although research on gaming has focused on children, a systematic review of health gaming research by Kharrazi, Lu, Gharghabi, and Coleman [6] found that out of 108 studies, 65 included participants no older than 20.…”
Section: Introductionmentioning
confidence: 99%